2014
DOI: 10.1111/cge.12361
|View full text |Cite
|
Sign up to set email alerts
|

Search for ReCQL4 mutations in 39 patients genotyped for suspected Rothmund–Thomson/Baller‐Gerold syndromes

Abstract: Three overlapping conditions, namely Rothmund-Thomson (RTS), Baller-Gerold (BGS) and RAPADILINO syndromes, have been attributed to RECQL4 mutations. Differential diagnoses depend on the clinical presentation, but the numbers of known genes remain low, leading to the widespread prescription of RECQL4 sequencing. The aim of our study was therefore to determine the best clinical indicators for the presence of RECQL4 mutations in a series of 39 patients referred for RECQL4 molecular analysis and belonging to the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…Piard et al reported that no RECQL4 mutations were found in their BGS group without poikiloderma. However, our patient had café-au-lait-like spots but not poikiloderma (8). The relationship between poikiloderma and RECQL4 gene mutation should be further examined.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Piard et al reported that no RECQL4 mutations were found in their BGS group without poikiloderma. However, our patient had café-au-lait-like spots but not poikiloderma (8). The relationship between poikiloderma and RECQL4 gene mutation should be further examined.…”
Section: Discussionmentioning
confidence: 70%
“…This rarity of BGS makes its diagnosis difficult in some cases. Piard et al (8). Showed that the mean age at referral for BGS was 7 years.…”
Section: Discussionmentioning
confidence: 99%
“…Rothmund-Thomson syndrome carries an increased risk for skin cancer, osteosarcoma and lymphoma. 9 Patient 4 was born with a cleft palate, micrognathia, and ocular hypertelorism. She had poor oromotor skills and mild deficits in motor development as she rolled at 8 months, sat at 10 months, and walked at 18 months.…”
Section: Patientsmentioning
confidence: 99%
“…Piard et al, 9 Rathi et al, 42 Siitonen et al, 43 Van Maldergem et al, 44 48 1978 Note: Table III notes cancer predisposition syndromes that may have craniofacial features that could trigger early referral to a craniofacial team before other symptoms are evident. The craniofacial manifestations are not seen in all patients and may be variable or absent.…”
Section: Recql4mentioning
confidence: 99%
“…Wang et al (2001). Esta positividade está de acordo com os dados da literatura, mostrando uma positividade que varia entre 40 e 60% (SUTER et al, 2016;PIARD et al, 2015;SIITONEN et al, 2009;CABRAL et al, 2008 (ZHANG et al, 2016;SUTER et al, 2016;PIARD et al, 2015;FRADIN et al, 2013;SIMON et al, 2010;SIITONEN et al, 2009;CABRAL et al, 2008;SZNAJER et al, 2006;KELLERMAYER et al, 2005;BEGHINI et al, 2003). (Wang et al, 2003).…”
Section: Síndrome De Hutchinson-gilfordunclassified